REPRESENTASIANAK KALIMAT DALAM TEKS BERITA POLITIK PILPRES PADA SURAT KABAR KOMPAS EDISI OKTOBER 2018 s.d MARET 2019 - Diana Mayasari (STKIP PGRI Jombang, 2019)
The journalist task has shifted from the news transmitter to the news formator and instructor. It shows that in writing news, journalist adds various comment, opinion and review that are difficult to distinguish from the news itself. A journalist should have a variety of rights and obligations, namely to deliver news in accordance with fact without mixing opinion.This study aims to reveal and expose the hidden aspects behind an apparent reality.This research methodology uses a qualitative descriptive approach. A qualitative approach is a research procedure that produces descriptive data in the form of the phenomenon description contained in the data. The data collected is in the form of newspaper document.The result of study shows that there is finding regarding representation, namely association and metaphor. The association was appeared in the news of compass newspaper by journalist to bring assumption in the mind of public in interpreting a certain reality regarding the debate between Jokowi and Prabowo. Journalist brings up how Prabowo take an action against Jokowi which is marked by transitive sentence namely subject + verb + object. Bring up a general symptom or phenomenon that occurs in the society regarding the legislative candidate photo displayed along the road. The form of participant as victim or object can be known from the construction of passive sentence, or victim caused by other.